RANCANG BANGUN MARKETPLACE STUDIO PHOTO DI KOTA PADANG MENGGUNAKAN FRAMEWORK CODEIGNITER - Dony Novaliendry; Nazifa Dwi Putri (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Marketplace is an activity forum that carries out buying and selling transactions in electronic form and the transaction process is very easy and fast. However, there is still little use of technology in marketing and searching for photo studio services, perhaps only limited to using social media such as Instagram, WhatsApp and Facebook. For now it is not easy to find photo studio services with good quality and affordable prices, because there are still few systems that provide detailed information about many photo studios. In addition, from the perspective of service actors, it is still difficult to market their services because they are obstructed by the information media. This marketplace design aims to find out how to promote, order and pay at the photo studio marketplace in Padang City. The design of this marketplace is built on a web basis using the CodeIgniter framework. This application was developed using the Unified Modeling Language (UML) model / method. As a result, it can provide fast service for customers because ordering and payments can be made online.